2017
DOI: 10.1038/s41467-017-01541-0
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for xenobiotic extrusion by eukaryotic MATE transporter

Abstract: Mulitidrug and toxic compound extrusion (MATE) family transporters export xenobiotics to maintain cellular homeostasis. The human MATE transporters mediate the excretion of xenobiotics and cationic clinical drugs, whereas some plant MATE transporters are responsible for aluminum tolerance and secondary metabolite transport. Here we report the crystal structure of the eukaryotic MATE transporter from Arabidopsis thaliana, at 2.6 Å resolution. The structure reveals that its carboxy-terminal lobe (C-lobe) contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
66
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(76 citation statements)
references
References 42 publications
6
66
1
Order By: Relevance
“…The outward-facing cavity was substantially shallower and narrower than the inward-facing cavity, and thus cannot accommodate the head group of Lipid II. This suggests that our outward facing structure represents a state in which the head group of Lipid II is released into the periplasm, consistent with the idea that cavity shrinkage could be a mechanism to displace substrate into the periplasm 32,34 (Fig. 4a).…”
Section: Outward-facing Conformation Of Murjtasupporting
confidence: 84%
See 1 more Smart Citation
“…The outward-facing cavity was substantially shallower and narrower than the inward-facing cavity, and thus cannot accommodate the head group of Lipid II. This suggests that our outward facing structure represents a state in which the head group of Lipid II is released into the periplasm, consistent with the idea that cavity shrinkage could be a mechanism to displace substrate into the periplasm 32,34 (Fig. 4a).…”
Section: Outward-facing Conformation Of Murjtasupporting
confidence: 84%
“…Furthermore, the questions of whether MurJ is an ion-coupled transporter and which ion(s) are involved remain unresolved. While some drug exporters in the MOP superfamily have been characterized to be Na + or H + coupled 12,[30][31][32] , our high-resolution inward-facing MurJ structure did not reveal a cation that could be important for transport 25 . It has been shown that MurJ activity is dependent on membrane potential and not on a H + gradient 33 , but the involvement of Na + has not been ruled out.…”
Section: Main Textmentioning
confidence: 57%
“…the NorM, DinF, and eukaryotic subfamilies (Omote et al, 2006). Over the last decade, structural and biochemical analyses of MATE transporters have been intensively pursued (Miyauchi et al, 2017;Tanaka et al, 2013Tanaka et al, , 2017He et al, 2010;Lu et al, 2013aLu et al, , 2013bMousa et al, 2016;Radchenko et al, 2015). To date, the crystal structures of five prokaryotic MATE transporters have been reported: Vibrio cholerae NorM subfamily (NorM-VC) (He et al, 2010) simultaneously coupled to the Na + and H + gradients (Jin et al, 2014), two Na + -driven MATE transporters (Neisseria gonorrhoeae NorM [NorM-NG] [Lu et al, 2013a] and Escherichia coli DinF subfamilies [ClbM] [Mousa et al, 2016]), and two H + -driven MATE transporters (Pyrococcus furiosus DinF [PfMATE] and Bacillus halodurans DinF subfamilies [DinF-BH] [Lu et al, 2013b;Radchenko et al, 2015]).…”
Section: Introductionmentioning
confidence: 99%
“…Based on their amino acid sequence similarity, the MATE family members are classified into the NorM, the DNA damage-inducible protein F (DinF), and the eukaryotic subfamilies (2). In recent years, the crystal structures of representative members of all three subfamilies have been published (7)(8)(9)(10)(11)(12)(13)(14)(15). Since all of them represent only an outward-facing state, a detailed understanding of the complete transport cycle has remained elusive.…”
mentioning
confidence: 99%